Muslim communities and cultures of the Himalayas: conceptualizing the global Ummah - Fewkes, Jacqueline; Sijapati, Megan Adamson (Routledge South Asian religion series, 2021)
"This book explores individual perspectives and specific iterations of Muslim community, Muslim practice and experience of Islam in the Himalayan region as well as the concept of the general Islamic community the Ummah. A multidisciplinary analysis of Muslim communities and historical and contemporary Islamicate traditions, the book shows how Muslims understand and mobilize regional identities and religious expressions. Moreover, it assesses regional interactions, the ways in which institutions shape Muslim practices in specific areas and investigates the notion of the Himalayas as an Islamic space. The book suggests that the regional focus on the Himalayas provides a site of both geographic and cultural crossroads where Muslim community is simultaneously constituted at multiple social levels. As a result, chapters document a wide range of local, national, and global interests while maintaining a focus on individual perspectives, moments in time, and localized experiences. This book draws attention to the cultural, social, artistic, and political diversity of the Himalaya beyond the better-understood and frequently documented religio-cultural expressions of the region. It will be of interest to academics in the fields of anthropology, geography, history, religious studies, Asian Studies, and Islamic Studies"--